Economische instrumenten voor de regulering van de geluidshinder in de omgeving van luchthavens? - Thierry Bréchet; Pierre Picard; Frédéric Dobruszkes (Brussels Studies, 2007)
One objective of Brussels Studies is to encourage debate around scholarly articles containing proposals for public action. With this issue, under the heading “double vision”, we are inaugurating a new formula – a dialogue between academics from different disciplines – in this case two economists and a geographer ‑ on the highly controversial issue of noise pollution caused by air traffic at Brussels National. The former propose creating a market for noise emissions as a regulatory instrument, while the latter evokes political responsibility to regulate the matter, based on the principle of limiting the number of people submitted to noise from aircraft.